PERSEPSI ORANGTUA TERHADAP ANAK BERKEBUTUHAN KHUSUS (Deskriptif Kuantitatif di SDLB N.20 Nan Balimo Kota Solok) - Rima Rizki Anggraini (Universitas Negeri Padang, 2013)
The study is in the background, background different attitudes of parents of children with special needs in SDLB N.20 Nan Balimo Solok City. The purpose of this study was to obtain an overview of the perception of parents of children with special needs that exist in SDLB N.20 Nan Balimo Solok City. The methodology of this research is descriptive quantitative approach. The sampling technique is the total sampling with a sample of twenty-nine parents of children with special needs. Techniques of data collection through a questionnaire distributed using Guttman scale with response alternatives exist, no and yes. From the above result revealed that parental perceptions or attitudes about the reaction that occurs in the presence of ABK received 34,4%, the perception of parents about how to eliminate negative attitudes toward ABK 86,2%, perceptions about foster parents develop a positive attitude toward ABK 58,7%, the perception of parents about the need for ABK which is basically no different from non ABK 48,2% children, parental perception of the role set ABK 34,4% parents, parents perception of the need for for implementation guidance to parents ABK 44.9%. suggested to parents to pay attention to the needs of children with special needs.